PERANCANGAN DESAIN POSTER EDUKASI WISATA AGRO LEMBAH KECUBUNG DESA PENANGGUNGAN KECAMATAN TRAWAS: DESIGN OF EDUCATIONAL POSTER DESIGN FOR AGRO LEMBAH KECUBUNG TOURISM IN PENANGGUNGAN VILLAGE TRAWAS DISTRICT - Aldila Mahadevi Akhadiyatni; Restu Ismoyo Aji (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Wisata Agro Lembah Kecubung is the first educational tour in Penanggungan Village, this Desa Wisata has the main attraction of education through natural rides, such as vegetable picking, water tubing, to water rides such as water duck ponds, fish ponds, fish therapy, and Lembah Kecubung Resto. Communication facilities in the form of educational posters are also important in a tour that can be used as one of the educational communication tools for visitors. Bina Desa Trawas MBKM Universitas Pembangunan Nasional “Vetran” Jawa Timur aims to design an educational poster design in the Wisata Agro Lembah Kecubung  to make it easier for visitors to understand information with the hope that visitors understand plant and animal information contained in the Amethyst Valley Agro Tourism. The research method used is descriptive analysis, and field surveys, the results obtained are data on plants located in tourist attractions with other data retrieval through journals and articles on information from plants and related animals.